The role of sonographic evaluation of spinal canal in children - Zupančič, Živa (Radiology and oncology (Ljubljana), 2000)
Background. Spinal sonography is a valuable diagnostic imaging modality as it has the ability to demonstrate good anatomic detail of the spinal canal, its contents, and the surrounding structures. The examination technique, the anatomy of the cord, the most common anomalies, and the evaluation of the sonography compared to magnetic resonance imaging are presented. Conclusions. Spinal sonography is recommended as the primary imaging modality for congenital anomalies of the lower spine in infants and as the screening modality for closed spinal dysraphism in infants and small children. The examination technique, the anatomy of the cord, the most common anomalies, andthe evaluation of the sonography compared to magnetic resonance imaging arepresented.
Keywords: Abnormalities; anatomija; Anatomy and histology; anomalije; Child; diagnostika; hrbtenični kanal; Infant; Lipoma; Magnetic resonance imaging; Meningomyelocele; otroci; Spina bifida occulta; Spinal canal; Spinal dysraphism; Ultrasonography